program Co - Chair_CLONE - Kyriacou, Efthyvoulos C. (My University, 2026)
Program Co-Chair : CAIP 2023 - The 20th International Conference on Computer Analysis of Images and Patterns, Sept 26-28, lemesos, Cyprus, 2024